Early Grade Mathematics in Ethiopia: Alignment of Contents in the Textbooks with the Corresponding Syllabuses - Tsebella, Aynalem Tesfaye; W/Yesus, Kassa Michael; Kassa, Solomon Areaya (Asian Journal of Education and Training, 2022)
An alignment of textbooks with their corresponding syllabuses contributes to effective learning. This study examined the alignment of the Ethiopian early grade (grades 1-4) mathematics textbooks (EEGMTB) with their corresponding syllabuses. Four early grade mathematics teachers at Halaba Zone of South Nations and Nationalities Peoples Reginal State (SNNPRS) participated in this study. In addition, curriculum experts at the zone and the ministry of education (MoE) participated. Data were collected through interview and document analysis by using a content analysis protocol developed by reviewing different studies on textbook quality (Bhatti, Jumani, & Bilal, 2015; Fuchs, 2013; Hashmi, Hussain, & Shoaib, 2018; Sunday, 2014; Taye, 2011), and validated. The data were analyzed qualitatively and the percentage was used to summarize the findings. The findings of this study depict that EEGMTBs were not completely aligned with the corresponding syllabuses as expected. Therefore, the study recommends special focus to be given to the alignment of textbooks with the corresponding syllabuses, especially in considering the learning outcomes when developing the textbooks. The study also suggests further research on the adequacy of the contents of early grade textbooks to equip early children with the necessary knowledge and skills expected at the level.